2022
DOI: 10.7759/cureus.24790
|View full text |Cite
|
Sign up to set email alerts
|

Left Main Coronary Artery Fusiform Aneurysm

Abstract: Aneurysm of the coronary artery is an uncommon condition that is usually found incidentally. The left coronary aneurysm is the least common. We report the case of a young patient with a history of vasculitis who was found to have a left fusiform coronary aneurysm. This is a 20-year-old female who has a history of polyarteritis nodosa and who came due to shortness of breath associated with chest discomfort. The physical exam was only relevant for multiple joint pains and tenderness. An echocardiogram showed a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…8 In addition, the use of statins is recommended due to their pleiotropic effects. 3 Similar to these recommendations, we discharged our patient with acetylsalicylic acid and atorvastatin, and we did not experience any complications during the follow-up. It is suggested that last-generation drug-eluting stents (DES) can be preferred as percutaneous treatment.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…8 In addition, the use of statins is recommended due to their pleiotropic effects. 3 Similar to these recommendations, we discharged our patient with acetylsalicylic acid and atorvastatin, and we did not experience any complications during the follow-up. It is suggested that last-generation drug-eluting stents (DES) can be preferred as percutaneous treatment.…”
Section: Discussionsupporting
confidence: 63%
“…The presence of CAA is associated with poor long-term prognosis independent of coronary artery disease. 3 In our case, we present a successful CABG operation performed on a patient who presented with chest pain and was found to have an aneurysm in the LMCA and LAD in the CAG and with accompanying critical CAD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation